Sozialraum Hochhaus Nachbarschaft und Wohnalltag in Schweizer Großwohnbauten - Althaus, Eveline (Urban Studies, 2018)
About living in high-rises built during the construction boom years, the potency of social marginalization and the resilience of neighborhoods.